2022
DOI: 10.1155/2022/9959649
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prognostic Factors for BRAFV600E Mutations in Papillary Thyroid Carcinoma

Abstract: Background. Over the past ten years, the incidence rate of papillary thyroid carcinoma (PTC) worldwide has been increasing rapidly year by year, with the incidence rate increasing 6% annually. PTC has become the malignant tumor with the highest growth rate in the world that fourteen PTC-related mutant genes have been identified. Whether the BRAFV600E mutation related to more aggressive clinicopathologic features and worse outcome in PTC remains variable and controversial. We aim to investigate the risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 79 publications
3
27
3
1
Order By: Relevance
“…The included cases were TNM stage I to stage II, which are relatively early stages. A recent meta-analysis of 9,908 patients with PTC ( 16 ) indicated that late TNM staging (stage III and IV) was an important risk factor for the BRAF V600E mutation in PTC patients. Additionally, the results of this study also indicated that there was no association between or increased risk for tumor size >1 cm and the BRAF V600E mutation in PTC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included cases were TNM stage I to stage II, which are relatively early stages. A recent meta-analysis of 9,908 patients with PTC ( 16 ) indicated that late TNM staging (stage III and IV) was an important risk factor for the BRAF V600E mutation in PTC patients. Additionally, the results of this study also indicated that there was no association between or increased risk for tumor size >1 cm and the BRAF V600E mutation in PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…facilitates the determination of benign or malignant thyroid nodules that cannot be diagnosed by FNAB alone, effectively improving the accuracy of the clinical diagnosis of thyroid nodules (14). Many studies have found that PTC patients with the BRAF V600E mutation often have high disease invasiveness and poor prognosis, thus making it a valuable prognostic marker of the disease (13,(15)(16)(17)(18)(19).…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…Even though the status and exact mechanisms are still unclear, a high prevalence status may indicate a new treatment area exploration concerning this specific mutation. Previously, the BRAF V600E mutation focused on malignant tumours, where the prevalence was approximately 74.6% for papillary thyroid carcinoma [ 95 ], 7.4% for colorectal cancer [ 96 ], and 60% for melanomas [ 97 ]. According to previous studies, several gene mutations have been identified in the background of BRAF V600E positive mutation in ameloblastoma, including somatic mutation in cyclin-dependent kinase inhibitor 2A ( CDKN2A ), catenin beta 1 ( CTNNB1 ), fibroblast growth factor receptors ( FGFR ), Kirsten rat sarcoma virus ( KRAS ), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha ( PIK3CA ), and phosphatase and tensin homolog ( PTEN ) [ 19 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since there is a lack of definitive evidence on the clinicopathological significance of BRAF V600E in adult PTC, several meta-analyses have been conducted to elucidate its role in the diagnosis, management and prognosis of aggressive PTC cases. Various associations have been reported between the presence of BRAF V600E mutation and demographic data or risk factors, such as tumor size, multifocality, lymph node metastasis, vascular invasion, extra-thyroid extension, and advanced stage of tumor node metastasis [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%